THE EFFECT OF USING AUGMENTED REALITY (AR) BASED MAZEDENT MEDIA ON THE LEVEL OF DENTAL AND ORAL HEALTH KNOWLEDGE OF CHILDREN WITH MILD INTELLECTUAL DISABILITY - aldila, sari; Arifin, Nur Fadhilah; Magfirah, Nurul (Universitas Baiturrahmah, 2025)
Background: Dental health is one part of child growth and development that needs to be considered. Mazedent Based on AR (Augmented Reality) is a game application that displays 3D objects and voice overs about dental and oral health which is useful as a learning and educational media to provide information for children with mild intellectual disability. This game application was created as a learning media for dental and oral health. Method: The type of research used was pre-experimental with a pre-test and post-test group design. A questionnaire was created to measure the knowledge of children with mild intellectual disability at SLB Negeri 1 Makassar and SLB Arnadya regarding dental and oral health before and after using Mazedent Media Based on AR (Augmented Reality). Results: Based on the results of the study, it was found that the average interpretation of 3 questions could be answered yes by the subjects before being given learning and after being given learning the ability to answer yes the subjects were an average of 12 questions, this showed an increase in the subjects. Conclusion: The results of the Wilcoxon test have a p value of 0.000 < (0.05), so it can be concluded that there is an influence of AR (Augmented Reality)-based Mazedent Media as a learning medium for dental and oral health for children with mild intellectual disability at SLB Negeri 1 Makassar and SLB Arnadya.